An Assessment of Management Support Provided to Construction Equipment Operators Regarding Safety Practices and Protocols in Nigeria - HASSAN, Usman (FUDMA Journal of Engineering and Technology, 2026)
Construction equipment operators in developing countries, such as Nigeria, frequently encounter significant health and safety challenges on job sites. These challenges are often exacerbated by factors that lead to substandard safety practices and inadequate risk management. While existing research has broadly established a relationship between management support and safety attitudes among general construction workers, a critical knowledge gap remains regarding how this relationship specifically affects construction equipment operators, a group exposed to unique operational risks due to their direct interaction with heavy machinery. This study assessed the perceptions of construction equipment operators regarding management engagement in enhancing safety attitudes within the Nigerian construction industry, thereby addressing this gap. The Nordic Occupational Safety Climate Questionnaire (NOSACQ-50) was utilized due to its validated reliability, cross-industry applicability, and comprehensive coverage of seven key safety climate dimensions, including management safety priority, empowerment, and justice, which are essential for holistically evaluating management support in high-risk construction environments. Data were collected from a sample of 107 construction equipment operators across selected construction sites. The results indicate moderate levels of management support, with mean scores of 3.24 for safety prioritization, 3.76 for safety empowerment, and 2.89 for safety justice. While respondents acknowledged management's efforts in risk prevention and problem-solving, significant gaps were identified in effective communication of safety measures, consistent enforcement of safety protocols, and consideration of workers' input in safety decisions. Furthermore, findings reveal that fear of sanctions discourages the reporting of near-miss incidents, indicating a weak safety justice system. These shortcomings undermine the overall safety climate and increase exposure to workplace risks. Based on the findings, the study recommends strengthening management commitment, improving communication channels, enhancing worker involvement in safety decisions, and promoting a non-punitive reporting culture. Addressing these issues will foster a safer working environment and support the development of a proactive safety culture within the Nigerian construction industry.
Keywords: Construction managers; Health and safety; Equipment operators; Management support; Safety climate.